Branchinecta fueguina ... - Cohen, Rosa Graciela (Zenodo, 2008)
Branchinecta fueguina nov. sp. Type material. Deposited in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”. Holotype, temporary pond in Tierra del Fuego province (Argentina), 53°47'12'' S, 67°46'55'' W, male number: MACN-In 37498; date: January 23, 2001; collector: M. C. Marinone; Allotype, same collecting data as holotype, female (ovigerous), number: MACN-In 37499. Type locality. temporary pond by Route C, in front of Laguna de los Cisnes, behind Río Grande Airport (53°47'12'' S, 67°46'55'' W), Tierra del Fuego, Antártida e Islas del Atlántico Sur Province, Argentina. Etymology. The specific epithet is a toponym of Tierra del Fuego, from which the specimens came. Description. Male: Mean total length from front to end of the abdomen with uropods (cercopods) without setae: 16.9 mm (16.1–18.1 mm). Mean uropods (cercopods) without setae length: 1.3 mm (1.1–1.4 mm). Average ratio of “head + thorax” to “abdomen + uropods without setae”: 1.02. Pedunculate eye diameter: 0.6–0.7 mm. Antenna 1 as ... : Published as part of Cohen, Rosa Graciela, 2008, A new species of Branchinecta (Crustacea: Branchiopoda: Anostraca) from the Argentinian Tierra del Fuego, pp. 60-68 in Zootaxa 1884 on pages 61-67, DOI: 10.5281/zenodo.184274 ...